2003
DOI: 10.4067/s0034-98872003000800007
|View full text |Cite
|
Sign up to set email alerts
|

Estudio clínico y determinación de la parasitemia en un grupo de pacientes infectados por Trypanosoma cruzi de la región de Atacama, Chile

Abstract: Background: Trypanosoma cruzi infection is endemic in (Rev Méd Chile 2003; 131: 881-6).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…None of the non-endemic studies identified an association between parasite DNA detection in peripheral blood and CCC. Six studies reported greater positive PCR ratios among patients with CCC than in patients with ICD although differences did not achieve statistical significance ( 36 , 37 , 41 , 42 , 44 , 45 ). The remaining 4 studies reported a positive PCR rate that favored patients with ICD ( 38 40 , 43 ).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…None of the non-endemic studies identified an association between parasite DNA detection in peripheral blood and CCC. Six studies reported greater positive PCR ratios among patients with CCC than in patients with ICD although differences did not achieve statistical significance ( 36 , 37 , 41 , 42 , 44 , 45 ). The remaining 4 studies reported a positive PCR rate that favored patients with ICD ( 38 40 , 43 ).…”
Section: Resultsmentioning
confidence: 94%
“…They all were performed in endemic regions and found a greater PCR positivity between patients with CCC and ICD with OR s of 5.17 ( CI 1.06–25.36) and 3.48 ( CI 2.31–5.23). In one study, although a risk ratio (RR) of 4.45 was reported, it included both cardiac and digestive forms on the analysis, and when OR was calculated with only CCC patients, we could not achieve statistical significance ( 36 ). None of the non-endemic studies identified an association between parasite DNA detection in peripheral blood and CCC.…”
Section: Resultsmentioning
confidence: 99%